A profile of diabetes in Pacific Island Countries and Territories. Issue 2 (February 2015) - Win Tin, Si Thu; Lee, Crystal Man Ying; Colagiuri, Ruth
Abstract: Aim: To examine the available evidence about the epidemiology, health, social, and economic impact of diabetes in Pacific Island Countries and Territories (PICTs). Methods: We conducted a systematic review of the peer-reviewed literature published in English from January 1990 to January 2014, and relevant technical reports. Results: A total of 1548 articles were identified of which 35 studies of type 2 diabetes met the inclusion criteria. Eighteen technical reports were also included. We found no articles reporting on type 1 diabetes or gestational diabetes that met the inclusion criteria. The prevalence, risk factors and complications of diabetes were substantial. Diabetes prevalence rate of around 40% was common. Physical inactivity, overweight and obesity were leading risk factors. High rates of diabetes complications were reported e.g. up to 69% retinopathy. Poor clinical outcomes were also reported with over 70% not meeting glycaemic control targets and approximately 50% not meeting blood pressure and cholesterol targets. Conclusion: This review highlights the burden of diabetes in PICTs and the need for more intensive interventions to improve the quality and outcomes of diabetes care. Overall, further research is needed to monitor secular diabetes trends in PICTs using standardised criteria for diagnosing diabetes and its complications.